PENGGUNAAN MODIFIKASI ALAT PEMBELAJARAN DALAM MENINGKATKAN TEKNIK DASAR TOLAK PELURU - Lestari Putri Widuri; Mochamad Zakky Mubarok; Agi Ginanjar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study is to determine the effect of using modified learning tools on improving the basic technique of shot put. The research method used is an experimental method, specifically a pre-experimental design with a one-group pretest-posttest design. The participants in this study were 28 tenth-grade students at SMK NU Kelautan Kaplongan. The sampling technique used was purposive sampling. The research instrument utilized was a shot put test. The results of the study revealed that there was a significant effect of using modified learning tools on improving the basic shot put technique.